The Translation of Idiomatic Expressions in the Karonese Cultural Legend “Pustaka Sembiring” into English - Helti Margaretha Tarigan; Syahron Lubis; T. Thyrhaya Zein (LingPoet: Journal of Linguistics and Literary Research, 2021)
Abstract. This study is about the translation of idiomatic expressions in the Karonese cultural legend “Pustaka Sembiring” into English. An idiomatic expression is a combination of words that form figurative meanings, cannot be interpreted from the literal meaning of its forming words , and the meaning is bound to the context, so transferring meaning between two different cultures becomes a challenge for translators in implementing appropriate translation strategies. This research applied the descriptive qualitative method. The source of the research data was a legend entitled "Pustaka Sembiring", a Karo-language text contained in the book “Himpunan Buku Legenda Karo" pages 171-176 published by Dinas Pariwisata, Seni dan Budaya Kabupaten Karo (the Karo District Tourism, Arts and Culture Office) in 2007, and the translation into English translated by Sehati Mitha Sembiring. The purpose of this study was to identify translation strategies applied in translating the idiomatic expressions in the source text into English. Through data collection and discourse analysis, 56 idiomatic idiom were found and then identified based on Baker's (1992) strategies in translating idiomatic expressions. The results showed that the translator used three of four Baker’s strategies, namely: 1) Paraphrase (39 or 69.7%) as the most frequently applied strategy, 2) Using Similar Idioms, Different Forms (8 or 14.3%), 3) Using Similar Idioms, Similar Forms (1 or 1.8%). Omission strategy was not found. In addition, there was another translation strategy labeled as Literal Translation (8 or 14.3%) found.